The Worst Things in Life are Free: The Role of Free Heme in Sickle Cell Disease - Gbotosho, Oluwabukola T.; Kapetanaki, Maria G.; Kato, Gregory J. (Frontiers in Immunology, 2021)
Hemolysis is a pathological feature of several diseases of diverse etiology such as hereditary anemias, malaria, and sepsis. A major complication of hemolysis involves the release of large quantities of hemoglobin into the blood circulation and the subsequent generation of harmful metabolites like labile heme. Protective mechanisms like haptoglobin-hemoglobin and hemopexin-heme binding, and heme oxygenase-1 enzymatic degradation of heme limit the toxicity of the hemolysis-related molecules. The capacity of these protective systems is exceeded in hemolytic diseases, resulting in high residual levels of hemolysis products in the circulation, which pose a great oxidative and proinflammatory risk. Sickle cell disease (SCD) features a prominent hemolytic anemia which impacts the phenotypic variability and disease severity. Not only is circulating heme a potent oxidative molecule, but it can act as an erythrocytic danger-associated molecular pattern (eDAMP) molecule which contributes to a proinflammatory state, promoting sickle complications such as vaso-occlusion and acute lung injury. Exposure to extracellular heme in SCD can also augment the expression of placental growth factor (PlGF) and interleukin-6 (IL-6), with important consequences to enthothelin-1 (ET-1) secretion and pulmonary hypertension, and potentially the development of renal and cardiac dysfunction. This review focuses on heme-induced mechanisms that are implicated in disease pathways, mainly in SCD. A special emphasis is given to heme-induced PlGF and IL-6 related mechanisms and their role in SCD disease progression.